Metabolic risk factors and effect of alirocumab on cardiovascular events after acute coronary syndrome: a post-hoc analysis of the ODYSSEY OUTCOMES randomised controlled trial. Issue 5 (May 2022) - Ostadal, Petr; Steg, Philippe Gabriel; Poulouin, Yann; Bhatt, Deepak L; Bittner, Vera A; Chua, Terrence; Diaz, Rafael; Goodman, Shaun G; Huo, Yong; Jukema, Johan Wouter; Karpov, Yuri; Pordy, Robert; et al.
Summary: Background: Many patients with acute coronary syndrome have concurrent metabolic risk factors that affect risk of major adverse cardiovascular events (MACE). We aimed to assess the effects of the PCSK9 inhibitor alirocumab compared with placebo on MACE according to baseline metabolic risk factors. Methods: We performed a post-hoc analysis of the ODYSSEY OUTCOMES trial, which was a multicentre, double-blind, randomised controlled trial done in 1315 hospitals and outpatient clinics in 57 countries. Patients aged 40 years or older with recent acute coronary syndrome (ie, in the past 1–12 months) and elevated concentrations of atherogenic lipoproteins, despite high-intensity or maximum-tolerated statin treatment, were eligible for enrolment. Between Nov 2, 2012, and Feb 9, 2017, patients were randomly assigned (1:1) to 75 mg alirocumab by subcutaneous injection every 2 weeks or matching placebo, beginning 1–12 months after acute coronary syndrome and were followed up for a median of 2·8 years (IQR 2·3–3·4). Patients and investigators were masked to group assignment and treatment dose adjustment. The primary outcome was a composite of death from coronary artery disease, non-fatal myocardial infarction, fatal or non-fatal ischaemic stroke, or unstable angina requiring hospital admission. Analysis of MACE according to an ordinal number of metabolic risk factors was done post hoc. Metabolic risk factors were defined as blood pressure of at least 130/85 mm Hg or treatment with antihypertensive medication, triglyceride concentration of at least 150 mg/dL, HDL cholesterol concentration less than 40 mg/dL for men and 50 mg/dL women, fasting plasma glucose concentration of at least 100 mg/dL or treatment with glucose-lowering medication, and BMI of at least 30 kg/m 2 . Risk of MACE and effect of alirocumab were assessed according to the number of metabolic risk factors. ODYSSEY OUTCOMES is registered with ClinicalTrials.gov, number NCT01663402 . Findings: Of 18 924 patients, 3882 (41%) of 9462 in the alirocumab group and 3859 (41%) of 9462 in the placebo group had three or more metabolic risk factors. In the placebo group, MACE incidence increased monotonically with each metabolic risk factor from 7·8% (no risk factors) to 19·6% (five risk factors; HR 1·18, 95% CI 1·13–1·24 per metabolic risk factor). Alirocumab decreased relative risk of MACE consistently across categories defined by the number of metabolic risk factors (p interaction =0·77), but absolute risk reduction (aRR) increased with the number of metabolic risk factors (no risk factors aRR 0·7%, –1·81 to 3·29 vs five risk factors aRR 3·9%, –1·45 to 9·25; p interaction <0·001). Similarly, when patients with diabetes were excluded, the incidence of MACE in the placebo group increased from 7·7% in patients with no metabolic risk factors to 14·6% in those with five metabolic risk factors and aRR with alirocumab increased from 0·91% in patients with no metabolic risk factors to 3·82% in those with five factors. Alirocumab was well tolerated in all subgroups defined by the presence of metabolic risk factors. Interpretation: Accumulation of metabolic risk factors was associated with higher risk of MACE in patients with recent acute coronary syndrome. Alirocumab reduced MACE consistently, but aRR increased with number of metabolic risk factors. Funding: Sanofi and Regeneron Pharmaceuticals.